Behavior Study of Male Bligon Goats Kept on Individual and Colony Housing - I Gede Suparta, Budisatria; Panjono, Panjono; Ali, Agus (2014)
The study was conducted to identify the behavior of male Bligon goats kept in individual and colony housing. The animals consisted of 10 head of one year old male Bligon goats housed either individually or in colony housingwith groundnut straw used as feed. Five male Bligon goats were kept in individual housing, while five others were confined to colony housing for three months. The observations made included total time and frequency of feeding ad the time spent resting/laying, ruminating, urinating and defecating. Those parameters were observed for seven days over each month, with observations made for 24 hours a day, starting from 06.00h. The result indicated that Bligon goats kept on the individual housing fed significantly less frequently (P<0.01) and spent less time eating (11.13 ± 0.70 vs 20.80 ± 2.42 times), laying (18.47 ± 0.40 vs 30.67 ± 1.18 times), ruminating (12.20 ± 0.55 vs 22.94 ± 1.17 times), and urinating (10.37 ± 0.58 vs 14.47 ± 0.72 times) compared to Bligon goats kept under colony housing. , in contrast, the average time spent eating each meal (25.27 ± 1.35 vs 15.70 ± 1.93 min), laying on each occasion (42.84 ± 3.16 vs 28.68 ± 1.66 min) and ruminating on each occasion (34.63 ± 1.82 vs 19.33 ± 0.83 min) was significantly higher (P<0.01) in Bligon goats kept on individual housing. The total time spent eating, laying, ruminating and frequency of defecation did not significantly differ with type of housing. It is concluded that individual housing provided a more comfortable system for Bligon goats compared to colony housing as assessed through these behavioural responses. Key Words: Behavior, Goats, Individual, Colony housing